Habilidades sociales y desempeño académico de los estudiantes de la carrera de psicopedagogía de la Unach - Bolaños Donoso, Jessica Valeria (2024)
This research aims to analyze social skills and academic performance among students of the Psycho-pedagogy program at the National University of Chimborazo. Social skills play a fundamental role in the academic life of young people, influencing their social interaction. The methodology employed a quantitative approach, with a basic level and a descriptive scope, and was a cross-sectional study in terms of time; the data collection instruments used were Elena Gismero's "Social Skills Scale" and a self-designed questionnaire with a Likert scale to measure students' perceptions of their academic performance. The population for this research was the Psycho-pedagogy program of the Faculty of Human Education and Technologies at Unach, and the sample for this study was intentionally selected, comprising 60 students from the fifth and sixth semesters. For interpretation, the data were processed using Excel and Google Forms software, which allowed the identification that most students generally exhibited an acceptable level of social skills. Regarding academic performance, a representative percentage indicated satisfaction with their performance during the semester; however, the percentage of those who did not feel satisfied did not show a desire for self-improvement or to enhance their current academic situation.